2011
DOI: 10.1521/pedi.2011.25.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Parental Burden Associated with Borderline Personality Disorder in Female Offspring

Abstract: To identify aspects of parental burden associated with borderline personality disorder (BPD), an anonymous internet survey linked to BPD support websites was developed for parents to complete on their BPD offspring and unaffected siblings. The questions cover aspects of the child's life from pregnancy through young adulthood, and query about the impact of the child's BPD on six domains of the parent's life, including physical and emotional health, marriage, job, standard of living, social life, and career traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 34 publications
5
67
2
4
Order By: Relevance
“…Qualitative information in the present study, visually represented in the concept map, suggests that caring for a person with personality disorder significantly affects relationships, including conflict and concern between family members and isolation from friends, consistent with findings from previous qualitative research (Ekdahl et al, 2011;Giffin, 2008;Goodman et al, 2011). Future research and the development of new guidelines may benefit from empirically ex- ploring the interpersonal experience of caregiving to understand the relational dynamics potentially contributing to the experience of burden and mental health problems (Grenyer, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Qualitative information in the present study, visually represented in the concept map, suggests that caring for a person with personality disorder significantly affects relationships, including conflict and concern between family members and isolation from friends, consistent with findings from previous qualitative research (Ekdahl et al, 2011;Giffin, 2008;Goodman et al, 2011). Future research and the development of new guidelines may benefit from empirically ex- ploring the interpersonal experience of caregiving to understand the relational dynamics potentially contributing to the experience of burden and mental health problems (Grenyer, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…A cut-off score of 7 or more items has shown good sensitivity and specificity for the DSM-IV diagnosis of BPD (Zanarini et al, 2003). The MSI-BPD has been adapted in previous research for carers to endorse observed symptoms of the person with personality disorder (Goodman et al, 2011). For the 283 participants with complete data on this measure, the MSI-BPD-C had weak internal consistency (Cronbach's α = 0.46).…”
Section: Mclean Screening Instrument For Borderline Personality Disormentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, when BPD is compared with other mental disorders, it is among the leading causes of disability-adjusted life years (DALYs) in young people 9 . BPD is also a substantial financial burden for the families of young people, with estimated average costs per annum in the US of $14,606 out-ofpocket, plus $45,573 billed to insurance 10 . Fifth, the "first wave" of evidence-based treatments has demonstrated that structured treatments for BPD in young people are effective 4 .…”
mentioning
confidence: 99%
“…To reduce the likelihood of overlooking potentially relevant studies, I conducted a second search using the terms "personality disorder(s)" and "economic" or "cost(s)" and found one other study, also from the Netherlands (Soeteman et al, 2008). One study has examined the economic costs of BPD in the United States (Goodman et al, 2010), in contrast to the 15 studies that have examined the cost of bipolar disorder (Kleine-Budde et al, 2014).…”
Section: Economicsmentioning
confidence: 99%